No-Touch Pancreatectomy for Invasive Ductal Carcinoma of the Pancreas - Hirota, Masahiko; Ogawa, Michio (JOP. Journal of the Pancreas, 2014)
Background Pancreatectomy is the only effective treatment for cancers of the pancreas. Surgeons usually grasp tumors during pancreatectomy; however, this procedure may increase the risk of squeezing and shedding of the cancer cells into the portal vein, retroperitoneum, and/or peritoneal cavity. In an effort to overcome these problems, we have developed surgical techniques for no-touch pancreatectomy. Methods From April 2008 through September 2013, 52 patients have been operated on no-touch pancreatectomy for invasive ductal carcinoma of the pancreas by a single operator (M.H.). Among them, 40 received pancreatoduodenectomy (PD), and 12 did distal pancreatectomy (DP). Twenty two cases (42%) required SMV-PV resection. This is a study to see if pancreatectomy can be technically done using a no-touch surgical technique without deteriorating the post-operative prognosis. During the procedure, the pancreatic tumor is neither grasped nor squeezed by the surgeon. Furthermore, for improved dissection of the retroperitoneal tissue (leftward and posterior margins for PD and rightward and posterior margins for DP), we use a hanging and clamping maneuver and dissection behind Gerota fascia. Results Overall 2- and 5-year survival rates were 64 and 42% with mean follow-up periods of 34.4 months (range: 6-68 months). Recurrence free 2- and 5-year survival rates were 49 and 31%, respectively. The 5-year survival rates of patients with JPS-stage III and those with JPS-stage IV were 57 and 20%, respectively. The 5-year survival rates of patients with UICC-stage IIA and those with UICC- stage IIB were 49 and 39%, respectively. Patients with UICC-stage III or IV did not survive for more than 2 years. Conclusions No-touch pancreatectomy has many theoretic advantages that merit further investigation in future randomized controlled trials. Image: Tissue slice along the clamp.